EDUCATIONAL EFFECTIVITY OF POSTERS IN TECHNICAL EDUCATION OF SECONDARY SCHOOL PUPILS - DOSTAL, Pavel (Journal of Technology and Information Education, 2020)
Posters are traditional teaching aids and have been used in technical education for many years. But do they really have the expected educational effect? Do they still contribute to raising the knowledge level of children, whose perception is determined by digital technologies? The paper presents the results of a quantitative research on the educational effectiveness of posters with technical content, where the sample was represented by approximately 500 pupils of older school age. The main research method was a natural pedagogical experiment, where the application of created posters corresponded to the independent variable and the level of knowledge was assigned to the dependent variable. A statistically significant increase in knowledge during one-year experiment was indicated only for a poster containing the least amount of information.
Keywords: poster; educational effectivity; elementary school; research